The Role of Perivascular Adipose Tissue in Non-atherosclerotic Vascular Disease - Horimatsu, Tetsuo; Kim, Ha Won; Weintraub, Neal L. (Frontiers in Physiology, 2017)
Perivascular adipose tissue (PVAT) surrounds most large blood vessels and plays an important role in vascular homeostasis. PVAT releases various chemokines and adipocytokines, functioning in an endocrine and paracrine manner to regulate vascular signaling and inflammation. Mounting evidence suggests that PVAT plays an important role in atherosclerosis and hypertension; however, the role of PVAT in non-atherosclerotic vascular diseases, including neointimal formation, aortic aneurysm, arterial stiffness and vasculitis, has received far less attention. Increasing evidence suggests that PVAT responds to mechanical endovascular injury and regulates the subsequent formation of neointima via factors that promote smooth muscle cell growth, adventitial inflammation and neovascularization. Circumstantial evidence also links PVAT to the pathogenesis of aortic aneurysms and vasculitic syndromes, such as Takayasu's arteritis, where infiltration and migration of inflammatory cells from PVAT into the vascular wall may play a contributory role. Moreover, in obesity, PVAT has been implicated to promote stiffness of elastic arteries via the production of reactive oxygen species. This review will discuss the growing body of data and mechanisms linking PVAT to the pathogenesis of non-atherosclerotic vascular diseases in experimental animal models and in humans.